Comparison of the Expression Changes after Botulinum Toxin Type A and Minocycline Administration in Lipopolysaccharide-Stimulated Rat Microglial and Astroglial Cultures - Piotrowska, Anna; Popiolek-Barczyk, Katarzyna; Pavone, Flaminia; Mika, Joanna (Frontiers in Cellular and Infection Microbiology, 2017)
Botulinum neurotoxin type A (BoNT/A) and minocycline are potent drugs used in clinical therapies. The primary molecular mechanism of BoNT/A is the cleavage of SNARE proteins, which prevents cells from releasing neurotransmitters from vesicles, while the effects of minocycline are related to the inhibition of p38 activation. Both BoNT/A and minocycline exhibit analgesic effects, however, their direct impact on glial cells is not fully known. Therefore, the aim of the present study was to determine the effects of those drugs on microglial and astroglial activity after lipopolysaccharide (LPS) stimulation and their potential synergistic action. Our results show that BoNT/A and minocycline influenced primary microglial cells by inhibiting intracellular signaling pathways, such as p38, ERK1/2, NF-κB and the release of pro-inflammatory factors, including IL-1β, IL-18, IL-6, and NOS2. We have revealed that, in contrast to minocycline, BoNT/A treatment did not decrease LPS-induced release of pro-inflammatory factors in the astroglia. In addition, BoNT/A decreased SNAP-23 in both types of glial cells and also SNAP-25 expressed only in astrocytes. Moreover, BoNT/A increased TLR2 and its adaptor protein MyD88, but not TLR4 exclusively in microglial cells. Furthermore, we have shown the impact of BoNT/A on microglial and astroglial cells, with a particular emphasis on its molecular target, TLR2. In contrast, minocycline did not affect any of those factors. We have revealed that despite of different molecular targets, minocycline and BoNT/A reduced the release of microglia-derived pro-inflammatory factors. In conclusion, we have shown that BoNT/A and minocycline are effective drugs for the management of neuroinflammation by dampening the activation of microglial cells, with minocycline also affecting astroglial activity.